Age-related associations between substance use and sexual risk behavior among high-risk young African American women in the South. (September 2019) - Swartzendruber, Andrea; Brown, Jennifer L.; Sales, Jessica M.; Windle, Michael; Haardörfer, Regine
Abstract: Background: We assessed age-related associations between substance use and sexual risk behavior using data from three HIV prevention trials that enrolled young African American women. Methods: We used integrative data analysis to pool data from 1862 individuals aged 16–25 years. We used time-varying effect models to examine associations between substance use (alcoholic drinks per month, recent marijuana use, cigarettes smoked per day) and sexual risk behaviors (monthly frequency of vaginal sex, multiple sex partners, condomless sex), adjusting for the fixed effect of trial. Results: In models that included all three substances, cigarette smoking was not associated with any outcome. Alcohol quantity was associated with greater frequency of sex at all ages, an increased likelihood of having multiple sex partners from about age 17–24 years, and an increased likelihood of condomless sex after about age 18.5 years. Associations between alcohol quantity and sex frequency were relatively stable; associations with having multiple sex partners and condomless sex increased beginning at about age 22 years. Marijuana use was associated with greater sex frequency at approximate ages 16.5–24 years and an increased likelihood of having multiple sex partners at ages 18–24 years. Associations with sex frequency were relatively stable; associations with having multiple sex partners increased from about age 18 and peaked at about age 23 years. Conclusions: We observed developmentally-dependent relationships between both alcohol and marijuana and sexual risk behavior. The findings underscore the need to address substance-related sexual risk among young African American women and may inform optimal timing of intervention. Highlights: This study used existing data from young African American women in the South. We studied sexual risk outcomes by drug across adolescence and young adulthood. Alcohol and marijuana were associated with increased sexual risk in unique ways. Cigarette smoking was not associated with sexual risk in adjusted analyses. The findings may help inform optimal timing of prevention interventions.